Problematika dan Solusi Pelaksanaan Ekstrakurikuler Wajib Pendidikan Kepramukaan Berdasarkan Kurikulum 2013 di SDN 68 Kota Bengkulu - Samsurizal, Rama Fareza. S; Supriatna, Irfan (JURIDIKDAS, 2025)
This study aims to determine the problems and solutions for the implementation of Compulsory Scouting Education Extracurricular according to the 2013 Curriculum at SDN 68 Bengkulu City. The research instruments are in the form of observation sheets, interview sheets, questionnaire sheets, and documentation guidelines. The technical data analysis uses a Likert scale, the results of the respondents' answers are then summarized and analyzed using the percentage formula P = F / N x 100%. The results of the study found that the implementation of scouting education extracurricular activities at SDN 68 Bengkulu City has implemented all models, namely the Block, Actualization, and Regular models, but in its implementation it has not been optimal. This is due to several factors, the first is the lack of facilities and infrastructure. second, the lack of instructors and there are still teachers who have not participated in KMD, and the last is the problem of lack of funds for the implementation of scouting education extracurricular activities. Based on the results of the study, it can be concluded that the problems in the implementation of compulsory extracurricular scouting education at SDN 68 Bengkulu City are the lack of facilities and infrastructure, the lack of instructors, there are still teachers who have not participated in KMD, and lack of funds. The solution to these problems is to add facilities and infrastructure that are still lacking, add external instructors, send teachers who have not participated in KMD to participate in KMD and find other sources of funds to increase funds for the implementation of scouting activities.